Emergencies in Hemodialysis Patients - Shannon Toohey (eScholarship Publishing, University of California, 2016)
Audience: This classic team-based learning (cTBL) session is appropriate for medical students or emergency medicine residents. Introduction: Over 380,000 patients have renal failure in the United States and 90% of these patients are managed on hemodialysis. Hemodialysis patients have high rates of morbidity and mortality. Understanding the management of emergencies unique to these patients is essential for any emergency physician. Objectives: By the end of this session, the learner will: 1) describe primary dialysis complications; 2) construct a full differential for a dialysis patient presenting with complications; 3) formulate an appropriate treatment and resuscitation in an acutely ill dialysis patient; 4) plan appropriate disposition and utilization of consultants for dialysis complications. Methods: The format of this educational session is cTBL.